Processos reduplicatius en català i ritme prosòdic: de l’adquisició fonològica a la formació de mots - Lleó, Conxita (Caplletra. Revista Internacional de Filologia, 1995)
Reduplication has come to occupy a preferential position in non-linear studies of phonology and morphology. In familiar Catalan language we encounter instances of reduplication which, theoretically, have been assimilated in morphological reduplication. The present article focuses on these reduplications, which are compared with reduplicative processes in other languages and in childrens’ speech. It approaches the question of which is the most suitable description of these, and concludes with the possibility of using the most appropriate type of reduplication in any given language in order to extract its characteristic phonological features.